2018
DOI: 10.1002/app.46611
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of lignin‐based cationic dye‐flocculant

Abstract: Kraft lignin derivatives having cationic poly 2-(trimethylamino)ethyl methacrylate side chains were synthesized and their property as dye-flocculant was investigated. Lignin-based flocculants having three types of side chain densities and three types of side chain lengths were synthesized by esterification of the lignin hydroxyl groups with bromoisobutyryl groups, atom transfer radical polymerization using 2-(dimethylamino)ethyl methacrylate, and quaternization of the amino groups. Dye removal test was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…This could be mainly because of the electrostatic coupling between the cationic side chain (amine group) of the aminated lignin and the anionic sites of the DB 1 dye. 52 It is well known that pH affects the adsorption of most organic pollutants as well as the surface charges of adsorbents. To further confirm that electrostatic interactions are key mechanism of adsorptive removal of dyes in DB 1 dye in aqueous solutions, the effect of initial pH on the dye decolorization efficiency and zeta potential of aminated CELF lignin was evaluated within the pH range of ∼4.0 and 10.0 (Figure 8).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This could be mainly because of the electrostatic coupling between the cationic side chain (amine group) of the aminated lignin and the anionic sites of the DB 1 dye. 52 It is well known that pH affects the adsorption of most organic pollutants as well as the surface charges of adsorbents. To further confirm that electrostatic interactions are key mechanism of adsorptive removal of dyes in DB 1 dye in aqueous solutions, the effect of initial pH on the dye decolorization efficiency and zeta potential of aminated CELF lignin was evaluated within the pH range of ∼4.0 and 10.0 (Figure 8).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The abundance of hydroxyl groups present in the aromatic and aryl chains provide potential for functionalization, and several studies reported the chemical modification of lignin by covalent attachment of synthetic polymers and oils. The chemically modified lignin was developed into suitable products such as new dispersants, adhesives, surfactants, films, capsules, and microparticles. , Lignin was successfully modified by attaching poly­(ε-caprolactone), , urethane groups, poly­(glycidyl methacrylate)- co -poly­(ethylene glycol)­methacrylate (PGEA-PEGMA), maleimido undecylenic acid, , epoxy groups reacted with poly­(ethylene glycol) diglycidyl ether, succinic anhydride or dodecyl-succinic anhydride (DSA), cyclic carbonates (ethylene carbonate, propylene carbonate, vinyl ethylene carbonate, and glycerol carbonate), , poly­(lactic acid), poly 2-(trimethylamino) ethyl methacrylate, and fatty acids . The chemically modified lignin showed better performance when compared to the blended lignin due to the contributions of the new attached moieties, which enhanced lignin solubility in organic solvents, stability in solution and UV light resistance, targeting, drug loading, and hydrophobic and hydrophilic balance. …”
Section: Introductionmentioning
confidence: 99%
“…Dye removal tests were carried out with three kinds of organic dyes: RBB, DR, and AB (Additional file 1: Figure S1) at room temperature (25 °C) [15]. Each dye was dissolved in water (100 mg/L) and 7 mL of the solution was placed in a test tube together with a volume of the GTA-HSAL solution containing the desired amount of nitrogen, calculated from the results of the nitrogen elemental analysis.…”
Section: Gta-hsal Dye Removal Testmentioning
confidence: 99%
“…Thence, develop an environmental friendly and high-efficient dry flocculant become a top priority. Additionally, the aromatic backbones, with hydroxyl groups and molecular weight around 4-17 kDa [14], of the water-soluble HSALs show great potential as matrix molecules for synthesizing effective flocculants for binding and precipitating ionic substances in water [15].…”
Section: Introductionmentioning
confidence: 99%